(untitled) (Iraqi National Journal of Earth Science (INJES), 2026)
The present study deals with the sequences existing between Pila Spi and Fatha formations in the Dehghan anticline, north of Mosul City, northern Iraq. These sequences are found to be at the late Oligocene - early Miocene age. These sequences consist of limestone and dolomitized limestone rocks. Petrographically, they consist of skeletal grains, the most important of which are benthic foraminifera, molluscs, ostracods, corals, algae, echinoderms and bioclasts as well as non-skeletal grains represented by lithoclasts. These sequences were subjected to diagenetic processes, the most important of which are cementation and recrystallization, which led to the burial of some living features, as well as the process of dissolution, compression, silicification, dolomitization and the authigenic minerals. Six main microfacies are diagnosed, represented by the mudstone, wakestone, packstone, boundstone, Bafflestone and Rudstone microfacies, which in turn are divided into nine submicrofacies. The study of these facies and the biological and sedimentary evidence shows that these sequences were deposited in a shallow marine environment extending from the reef environment to the tidal flat environment.